Phytochemical study and bio activity from the stem bark of Shore a macroptera dyer / Nur Ainaa Atikah Mohd Nazri - Mohd Nazri, Nur Ainaa Atikah (2014)
Shorea macroptera from family Dipterocarpaceae was studied for its phytochemical and biological activities. Eight compounds have been isolated including two compounds in mixture which consists of nine resveratrol oligomers and an isoferrulic derivative. The compounds were identified as (^-pentacosyl 3-(3-hydroxy-4-methoxyphenyl) acrylate, E-viniferin, davidiol A, hemsleyanol D, hopeaphenol A, hopeaphenol, isohopeaphenol, stenophyllol B, gnetol and laevifonol. Gnetol is a monomer resveratrol, £- viniferin and laevifonol are dimer resveratrols, davidiol A and stenophyllol B are trimer resveratrols while hemsleyanol D, hopeaphenol A, hopeaphenol and isohopeaphenol are tetramer resveratrols. Structural elucidation was performed with the aid of spectroscopic methods such as ultraviolet (UV), infrared (IR), mass spectrometry (MS), ID and 2D nuclear magnetic resonance (NMR). Shorea macroptera extract and some of the isolated compounds have been tested for antioxidant, antibacterial and also cytotoxic activities. Shorea macroptera extract showed good antioxidant and antibacterial activities compared to individual isolated compounds, e-viniferin demonstrated marked cytotoxic activity which strongly inhibited HL-60 cell lines but moderately on HeLa cell lines. Davidiol A showed significant cytotoxic activities. It strongly inhibited HL-60 cell lines but moderately inhibited HeLa cell line. Hemsleyanol D moderately inhibited the growth of HeLa cell line. Hopeaphenol displayed significant free radical scavenging activity. Stenophyllol B was found active in free radical scavenging and cytotoxic activities. Stenophyllol B exhibited moderate free radical activity and moderately inhibited HL-60 cell lines and HeLa cell lines. However, laevifonol was inactive towards all three assay tested.